2012
DOI: 10.1155/2012/701704
|View full text |Cite
|
Sign up to set email alerts
|

Murine Models of B-Cell Lymphomas: Promising Tools for Designing Cancer Therapies

Abstract: Human B-cell lymphomas, the fourth most common hematologic malignancy, are currently the subject of extensive research. The limited accessibility of biopsies, the heterogeneity among patients, and the subtypes of lymphomas have necessitated the development of animal models to decipher immune escape mechanisms and design new therapies. Here, we summarize the cell lines and murine models used to study lymphomagenesis, the lymphoma microenvironment, and the efficacy of new therapies. These data allow us to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 78 publications
2
43
0
Order By: Relevance
“…In this paper, we are not aiming at assessing the efficacy of CpG as an anti-tumor drug (which has already been demonstrated 7,9,11 ) but to describe a method allowing comparison of bioluminescence datasets. We indeed describe a method to quantify tumor burden intended to help standardize the acquisition protocol for comparing different assays in different places at different times and that does not require computer calculations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we are not aiming at assessing the efficacy of CpG as an anti-tumor drug (which has already been demonstrated 7,9,11 ) but to describe a method allowing comparison of bioluminescence datasets. We indeed describe a method to quantify tumor burden intended to help standardize the acquisition protocol for comparing different assays in different places at different times and that does not require computer calculations.…”
Section: Discussionmentioning
confidence: 99%
“…We applied the luminoscore method to two different mouse lymphoma models 7,8,9 . CpG is an oligonucleotide sequence and a ligand of TLR9, which in turn is an intracellular receptor expressed by numerous cells of the immune system, including dendritic cells, B lymphocytes, monocytes, and natural killer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study indicated that treatment of mice inoculated with Ramos cells with 47 mg/kg of the test article CBPDA caused a significant reduction of the tumor growth in a 2-week treatment period in NOD-scid mice with experimental Ramos cell B [21][22][23][24][25][26][27][28][29][30]. The mean tumor volume of the treated animals was 53% of the mean tumor volume of the vehicle group.…”
Section: Discussionmentioning
confidence: 99%
“…Their therapeutic efficacy was tested in BALB/c mice bearing subcutaneous A20 lymphoma tumors. This syngeneic model mimics human disease in an immunocompetent host with aspects of diffuse large B-cell lymphomas, 28,29 which in our view is clinically relevant. The subcutaneous model has additional advantages, such as providing visual confirmation that mice do have tumors prior to therapy and easy assessment of tumor response or growth over time.…”
Section: Fa-tagged Protein Nanoemulsions Loaded With Corm-2 and Specimentioning
confidence: 92%